CFD simulation for air-conditioning environment using fluent with user-defined function - Ong, Aidan Jiong Shun (2017)
Singapore is known for having a tropical climate with hot and humid weather all year round. The abundance of high-rise buildings on this tiny red dot have led to wind obstructions and resulted in an undefined distribution of air flow. This effect affects urban resident’s summer discomfort and greatly increases air conditioning loads. With this rising concern, the national authorities have incorporated the “Heating, Ventilating and Air-Conditioning” (HVAC) system into residential structures to improve thermal comfort. However, this implementation can potentially lead to higher energy consumption and worsens global warming. Through the advancement of modern technology, Computational Fluid Dynamics (CFD) is used extensively today by researchers to investigate and analyse the expectancy of air flow flowing into the indoor buildings. The methodology of the numerical experiment is applied on ANSYS/Fluent software. Firstly, a geometric model is drawn based on two cases of two-dimensional configuration profiles, with and without heat source respectively. Next, the meshing considerations allow for refinement and enhancement on the mesh size, and the ‘Named selection’ feature function to state the design components. Subsequently, the boundary conditions for the input parameters such as the direction of air flow, range of time, air temperature and position of inlet and outlet differs for the respective two cases. Lastly, the setup in key parameters further improvises the iteration results, whereby timing is crucial for the generation of the contour and vector plots. User-Defined Function (UDF) is a written programme source code that controls the air flow velocity direction with respect to time and with the velocity magnitude remains constant. With the iterated results, the air flow velocity and the temperature of contour and vector plots are compared and discussed with no UDF, irreversible UDF and reversible UDF respectively. For further validation, the heat sources are identified as real life occupants are added in the numerical experiment to give more logical and realistic results. Therefore, the objective of this project study is to show through the two-dimensional configuration profiles room, that UDF is able to help achieve optimal air flow and thermal distribution.